Distribution of finances in the field of physical culture and sport using the example of the Ural Federal District - Naboychenko, E.S.; Yuzvovich, L.I.; Lvova, M.I.; Polyakova, E.Yu. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to assess the sources of funding for sports infrastructure facilities and the distribution of financial resources among projects at the regional level. Methods and structure of the study. Statistical and factor analysis, dynamic method, expert assessment method, and formulation of abstract logical content. Results and conclusions. It has been determined that financing physical culture in the Ural Federal District is a complex but dynamic process, combining the ambitions of industrial regions with the challenges of depressed areas. Despite the inequality in resources, the district is demonstrating success in creating infrastructure and supporting mass sports. The key conditions for further progress will be strengthening interregional cooperation, attracting private capital, and providing targeted support to areas with low living standards. Funding physical culture in the Sverdlovsk Oblast is a strategic direction that unites the efforts of the state, business, and society. Thanks to systematic investment, the region is not only improving the health of its population, but also nurturing new champions. However, in order to achieve maximum effect, it is important to continue diversifying sources of funding and to pay attention to the development of sport in small towns and villages.